2013
DOI: 10.1242/jeb.088104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection dynamics: using immunosuppression andin vivoparasite tracking to understand host resistance in an amphibian-trematode system

Abstract: SUMMARYAlthough naturally occurring hosts often exhibit pronounced differences in infection and pathology, the relative importance of factors associated with host life history and immunity in explaining such patterns often remains speculative. Research in ecoimmunology highlights the trade-offs between host physiology and immunity, for which natural variations in disease susceptibility offer a valuable platform to test predictions within this framework. Here, we combined use of a novel, in vivo assay for track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 78 publications
2
46
0
Order By: Relevance
“…The presence of malformed frogs has often prompted a subsequent examination to determine whether R. ondatrae is present; however, amphibian species vary in their propensity to develop malformations following exposure (Johnson et al 2012). In southern Ontario, only grey tree frogs ( Hyla versicolor ), green frogs ( Lithobates clamitans ), and American bullfrogs ( Lithobates catesbeianus ) have been detected at our field sites, all of which are highly resistant to R. ondatrae -induced malformations (Johnson et al 2012, LaFonte and Johnson 2013). While amphibian deformities have been reported in eastern Canada (Ouellet et al 1997), the role of R. ondatrae has not been specifically examined in relation to these observations, and has only been confirmed as a causative agent in a host species ( Pseudacris regilla ) restricted to western Canada (Roberts and Dickinson 2012).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The presence of malformed frogs has often prompted a subsequent examination to determine whether R. ondatrae is present; however, amphibian species vary in their propensity to develop malformations following exposure (Johnson et al 2012). In southern Ontario, only grey tree frogs ( Hyla versicolor ), green frogs ( Lithobates clamitans ), and American bullfrogs ( Lithobates catesbeianus ) have been detected at our field sites, all of which are highly resistant to R. ondatrae -induced malformations (Johnson et al 2012, LaFonte and Johnson 2013). While amphibian deformities have been reported in eastern Canada (Ouellet et al 1997), the role of R. ondatrae has not been specifically examined in relation to these observations, and has only been confirmed as a causative agent in a host species ( Pseudacris regilla ) restricted to western Canada (Roberts and Dickinson 2012).…”
Section: Discussionmentioning
confidence: 89%
“…As discussed above, grey tree frogs were primarily sampled in the southern Ontario wetlands, and are highly resistant to R. ondatrae infection (Johnson et al 2012). Because tadpoles of this species are capable of actively clearing cysts within 72 hours (LaFonte and Johnson 2013), collected hosts would have to represent recent infection events in order to detect R. ondatrae through necropsy. The eDNA results may therefore provide a more accurate assessment of parasite presence in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Infection success was similar in the experimental tadpoles exposed to R. ondatrae and the 15 tadpoles exposed but not introduced into mesocosms (see Results), but we cannot completely eliminate the possibility that individuals categorized as uninfected had lost their infections over the period of our experiment. However, larval P. regilla have a very low rate of R. ondatrae cyst clearance (Lafonte and Johnson 2013), and it is unlikely that individuals categorized as uninfected had lost their infections. We explored the importance of competitive ability by comparing developmental stage and likelihood of early emergence of uninfected tadpoles compet- ing against uninfected conspecifics in the no-parasitism mesocosms vs uninfected tadpoles competing against a mixture of infected and uninfected conspecifics in the parasitism mesocosms.…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
“…Recent evidence that amphibian hosts differ in the capacity to "clear" trematode parasites post-infection emphasizes the importance of quantifying temporal changes in infection load. For instance, LaFonte and Johnson (2013) showed that the median survival time of Ribeiroia metacercariae within amphibians could vary from 10 hrs to >600 hrs among different frog species (LaFonte and Johnson, 2013). Such observations have prompted growing interest in sub-lethal methods for quantifying parasite infections in vivo, such as qPCR of skin swabs to track chytridiomycosis infection at multiple time points (Herbert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such observations have prompted growing interest in sub-lethal methods for quantifying parasite infections in vivo, such as qPCR of skin swabs to track chytridiomycosis infection at multiple time points (Herbert et al, 2011). The use of fluorescently labeled parasites, for example, allows researchers to track both initial infection success as well as the subsequent fate of each colonizing parasite within living hosts over time, at least for parasites that are visible externally through the host tissue (Herbert et al, 2011;Keeney et al, 2008;LaFonte and Johnson, 2013). Because this technique is non-destructive, it also provides an opportunity to compare estimates of infection between different methods, thereby yielding measures of accuracy, precision and bias.…”
Section: Introductionmentioning
confidence: 99%